A Simplified Technique to Record Neutral Zone and Cameo Surface in Complete Denture - Aditi Nanda; Harsimran Kaur; Dheeraj Koli; Mahesh Verma (Wolters Kluwer Medknow Publications, 2024)
Introduction: Providing complete denture therapy to patients with atrophic residual alveolar ridges is challenging, because these patients suffer ongoing resorption of the denture foundation; regardless of contemporary treatment options, physiologically optimal denture contours and appropriate denture tooth arrangement should be achieved to maximize prosthesis stability, comfort and function for patients. One of the methods used to achieve the stability is the neutral zone technique. Aim: It is in this zone that the natural dentitions lie and this is where the artificial teeth should be positioned. This article describes a preview of faciolingual positioning of denture teeth along with a novel approach of recording the neutral zone. Conclusion: The neutral zone is the area where the displacing forces of the lips, cheeks and tongue are in balance. Physiologic recording of the neutral zone aids in stability to the prosthesis.